Analysis of Grammatical Morpheme Acquisition of Indonesian High School English Learners - Rina Astuti Purnamaningwulan (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2020)
L2 learners morpheme acquisition has been studied a lot subsequent to Dulay and Burts work(1974). Similar to other studies responding to Krashens (1977) notion on natural acquisitionorder, this small-scale research aims at investigating whether Indonesian high school English learners also go through similar acquisition order as the respective notion. The data taken froma group of Indonesian high school students writing assignment were analyzed using theObligatory Occasion Analysis (Ellis Barkhuzien, 2005) to investigate the grammaticalmorpheme acquisition order of the students. Subsequently, the finding was analyzed to seewhether the acquisition order was influenced by Krashens hypothesis. The findings showedthat the morpheme acquisition order of the research participants did not go through similaracquisition order as stated in Krashens natural order hypothesis. Further, the participants L1partially contributed to the order.